2018
DOI: 10.3906/tar-1710-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altitude, shooting period, and tea grade on the catechins, caffeine, theaflavin, and thearubigin of Turkish black tea

Abstract: The effect of altitude, shooting period, and tea grade on the catechins and caffeine contents of Turkish black tea was investigated. The experimental factors significantly affected all of the parameters analyzed. Epigallocatechin gallate was the major catechin of black tea (0.719-1.007 g 100 g -1 dm) followed by epigallocatechin (0.627-0.791 g 100 g -1 dm). Additionally, caffeine (1.810-2.175 g 100 g -1 dm), theaflavin (3.201-6.000 µmol g -1 ), and thearubigin (8.577-12.635 g 100 g -1 dm) contents were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
14
2
1
Order By: Relevance
“…The water content of EKKBP obtained in this study has met the specified extract water content standard. EKKBP water content in this study ranged from 9.93 to 10.96%, higher than the results of research Ozdemir et al (2018) the water content of catechin extracts in black tea ranged from 4.78 to 5.45%. Yunarto et al (2015) reported the moisture content of the ethyl acetate fraction of gambir leaf extract was 2.23%.…”
Section: Catechin Extractioncontrasting
confidence: 83%
“…The water content of EKKBP obtained in this study has met the specified extract water content standard. EKKBP water content in this study ranged from 9.93 to 10.96%, higher than the results of research Ozdemir et al (2018) the water content of catechin extracts in black tea ranged from 4.78 to 5.45%. Yunarto et al (2015) reported the moisture content of the ethyl acetate fraction of gambir leaf extract was 2.23%.…”
Section: Catechin Extractioncontrasting
confidence: 83%
“…The results showed that infusion time is only a critical parameter for black tea and moderately for oolong tea. For the reason that, low molecular catechins are oxidized to form high molecular weight polymers, TFs and TRs during fermentation . This resulted in the loss of TPC of the black tea and so the phenolic amount is found to be lower than other tea types.…”
Section: Resultsmentioning
confidence: 99%
“…In 100 g of skins, however, these contents were lower and ranged only from 660 to 1.839 mg of catechin equivalents. Values of antioxidant activity were assessed by DPPH and Ozdemir et al 2018]. The grapevine seed extract was rich both in oligomeric and polymeric flavanols.…”
Section: Assessment Of Isorhamnetin Isorhamnetin Is Anmentioning
confidence: 99%